Avian malaria, ecological host traits and mosquito abundance in southeastern Amazonia. Issue 8 (27th March 2017) - FECCHIO, ALAN; ELLIS, VINCENZO A.; BELL, JEFFREY A.; ANDRETTI, CHRISTIAN B.; D'HORTA, FERNANDO M.; SILVA, ALLAN M.; TKACH, VASYL V.; WECKSTEIN, JASON D.
SUMMARY: Avian malaria is a vector transmitted disease caused by Plasmodium and recent studies suggest that variation in its prevalence across avian hosts is correlated with a variety of ecological traits. Here we examine the relationship between prevalence and diversity of Plasmodium lineages in southeastern Amazonia and: (1) host ecological traits (nest location, nest type, flocking behaviour and diet); (2) density and diversity of avian hosts; (3) abundance and diversity of mosquitoes; and (4) season. We used molecular methods to detect Plasmodium in blood samples from 675 individual birds of 120 species. Based on cytochrome b sequences, we recovered 89 lineages of Plasmodium from 136 infected individuals sampled across seven localities. Plasmodium prevalence was homogeneous over time (dry season and flooding season) and space, but heterogeneous among 51 avian host species. Variation in prevalence among bird species was not explained by avian ecological traits, density of avian hosts, or mosquito abundance. However, Plasmodium lineage diversity was positively correlated with mosquito abundance. Interestingly, our results suggest that avian host traits are less important determinants of Plasmodium prevalence and diversity in southeastern Amazonia than in other regions in which they have been investigated.